Performance Optimization of High Voltage Thyristor Based on Vacuum Deposited Aluminum Diffusion Technology - YIN Dengjie; HE Zhenqing; LI Yong; JIAO Shasha (Kongzhi Yu Xinxi Jishu)
In the design of silicon parameters of high voltage thyristor device, the flatness of PN junction formed by different kinds of diffusion process is one of the key factors in the manufacturing. In order to obtain better dynamic and static characteristics of high voltage fast thyristor, starting with manufacturing process, the flatness difference of PN junction formed by vacuum deposited aluminum diffusion and close-tube aluminum diffusion process was discussed firstly, then through the theoretical calculation and Silvaco simulation, the relationship between the voltage of the device and the junction depth was obtained, and based on the consideration of the flatness of PN junction, the minimum thickness of silicon under two different conditions was designed. Experimental results showed that the performance optimization of the device was obvious based on the vacuum deposited aluminum diffusion technology and its optimum silicon parameters.